Seni Tari di Era Virtual dan Augmented Reality - Citrawati, A.A.I.A; Oktavianus; Nurmalena; Irdawati; Herwanfakhrizal (AI Society & STMIK Indonesia, 2024)
The art of dance has been revolutionized in the era of virtual and augmented reality (VR and AR), bringing about significant transformations in presentation, interaction and audience participation. This article explores the impact of these technologies on the art of dance, investigating how VR and AR are changing artists' creativity, enriching the audience experience, and enabling the development of new dance styles. In this context, dance is not only a witness to change, but also the main actor in combining traditional beauty with modern innovation. The method applied is